Beneficial Effect of Heat-Killed Lactiplantibacillus plantarum L-137 on Skin Functions in Healthy Participants: A Randomized, Placebo-Controlled, Double-Blind Study - Yoshitake, Rieko; Nakai, Hiroko; Ebina, Manato; Kawasaki, Kengo; Murosaki, Shinji; Hirose, Yoshitaka (Frontiers in Medicine, 2022)
To determine whether consuming heat-killed Lactiplantibacillus plantarum L-137 (HK L-137) influences skin functions, we performed a randomized, placebo-controlled, double-blind study in healthy participants who were conscious of dry skin. A total of 80 healthy participants (20 men, 60 women; mean age, 47.3 years) were assigned to receive a tablet containing HK L-137 or a placebo tablet daily for 12 weeks. Every 4 weeks, the skin water content and transepidermal water loss (TEWL) were measured at the forearm and face, and participants completed 2 skin-related questionnaires, the Dermatology Life Quality Index and a self-evaluation. The HK L-137 group tended to show greater increases from baseline of water content at the forearm and larger decreases of TEWL at the face. The total scores of both questionnaires improved significantly more in the HK L-137 group. Water content and TEWL improved significantly in participants in the HK L-137 group who were above the median age of study participants or had relatively dry skin. These findings suggest that daily HK L-137 intake can improve dry skin, thereby contributing to skin satisfaction.